Enhanced Activity and Selectivity in Catalytic Methanol Steam Reforming by Basic Alkali Metal Salt Coatings. Issue 19 (3rd April 2013) - Kusche, Matthias; Enzenberger, Florian; Bajus, Stephanie; Niedermeyer, Heiko; Bösmann, Andreas; Kaftan, Andre; Laurin, Mathias; Libuda, Jörg; Wasserscheid, Peter
Abstract : Tri‐salts added : Pt on alumina catalysts can be used for converting methanol and water into hydrogen and carbon dioxide (see picture), for applications such as hydrogen storage. Both the activity and selectivity could be enhanced by coating these materials with a thin layer of a molten salt mixture of Li/K/Cs acetate. Potassium doping was identified by DRIFTS measurements to be an important factor for the boost in catalyst performance.